PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KUALITAS LABA - Dul Muid (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
The objective of this research is to investigate impact of corporate governance to earning quality that the proxi of it with discretionary accruals. Corporate governance mecanism are managerial ownership, commisaries board, audit committee, and ownership institutional.The samples of this research is the manufacture company that listed in Jakarta Stock Exchange periode 2004 – 2005. Using purposive sampling was got 188 samples. The examine of the hypothesis used linear regression.The result of research indicate managerial ownership, commisaries board are significant to earning quality, but audit committee, and ownership institutional are not significant to earning quality.